PENGARUH DIGITAL MARKETING DAN WORD OF MOUTH TERHADAP LOYALITAS KONSUMEN MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA BAROKAH CATERING - Maisaroh, Nulfi (Publika Citra Media, 2025)
This study aims to examine the influence of digital marketing and word of mouth on consumer loyalty with consumer trust as an intervening variable in Barokah Catering. The population in this study is all Barokah Catering customers. The sample was selected using a purposive sampling technique with the criteria of customers who have used catering services at least once and are domiciled in Sumbawa Regency. This study uses a quantitative method with a causal associative approach. The data analysis technique was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS), with the number of respondents determined based on Paul Leedy's formula, which was 100 people. The results of the study show that digital marketing and word of mouth have a significant effect on consumer trust. However, digital marketing does not have a significant effect on consumer loyalty, while word of mouth has a significant effect on consumer loyalty. In addition, consumer trust does not have a significant effect on consumer loyalty and cannot be an intermediary variable in the relationship between digital marketing and word of mouth to consumer loyalty. These findings indicate that word of mouth strategies are more effective in increasing customer loyalty than digital marketing.